Abon Studi Pembuatan Bakpao dengan Bahan Pengisi Abon dari Variasi Kerang yang Berbeda Terhadap Uji Penerimaan Konsumen: Studi Pembuatan Bakpao dengan Bahan Pengisi Abon - Diana, Ayu; Lubis, Ahmad Fauzan; Fikri, Muhammad Zakiyul (PAKIS JOURNAL INSTITUTE, 2024)
Shellfish meat is a source of animal protein that has a more complete amount of amino acids than vegetable protein. Shellfish processing is still mostly done traditionally. The potential for shellfish to be developed into a food product is very large, but the biggest challenge is the characteristic that has a fishy smell, high elasticity, and texture that is not attractive. Bakpao products are selected to be combined with shredded shellfish filler to cover the texture and aroma that is less attractive in shellfish preparations. This study aims to determine the level of consumer acceptance of processed products bakpao with shredded shellfish filler variation. This research method is carried out in three stages. The first stage is the stage of preparation of raw materials for kerang lentera, kerang bulu, kerang tahu, and the manufacture of shredded shells. The second stage is the stage of making shredded-filled buns. The third stage of research is the stage of hedonic testing to determine consumer acceptance. The results obtained in the manufacture of shredded bakpao from different shellfish variations, namely kerang lentera (Lingula unguis), kerang bulu (Anantara antiquate), and kerang tahu (Meritix-meritrix) have their characteristics in taste, appearance, aroma, and texture so that they can get the value of consumer preferences. The results of the hedonic test in this study found that the best appearance test results are treatment P2 (5,05), the smell highest value is P2 (4,68), the best taste test is P2 (5,06), and the best texture value is P2 (5.23). Based on the overall results of a hedonic test that the highest preference value of the bakpao with different variations of shredded shellfish is bakpao with variations of shellfish feathers (P2).